Rhetorical Moves Used in MA Students’ Theses in TEFL and Nursery - Maryam Jamalzade Jahromi; Ehsan Hadipourfard; Leila Akbarpour (Research in English Language Pedagogy, 2023)
Abstracts in research papers are one of the focal parts of academic research, and they are one of the first things that a reader reads to determine the value of the research. Furthermore, acknowledgments appreciate those who have helped in writing a thesis. The present study investigated rhetorical moves in the acknowledgment and abstract sections of Iranian English language teaching and nursery students' M.A. theses. In addition, it investigated if there were any significant differences between rhetorical moves observed in the acknowledgment and abstract sections of Iranian TEFL and nursery students' M.A. theses in these two fields. Some of the 80 theses from the two disciplines, 40 each, were investigated. Hyland's (2000) models of the abstract rhetoric structure and acknowledgment structure were adopted to investigate the corpora under study. The results revealed that different steps and moves were used in theses from both disciplines. However, the results of Chi-square tests revealed that the differences between different moves and steps of these acknowledgments and abstracts from the two disciplines were insignificant. The findings have some implications for post-graduate students to be more aware of their addressees and language teachers to teach students about genre-based writing.